Synthesizing higher nitride of molybdenum (Mo) and iron (Fe) in ammonia (NH3) gas stream under irradiation of concentrated solar beam in a solar furnace - Shohoji, Nobumitsu (2014)
Flowing gaseous ammonia NH3 with suppressed extent of dissociation (un-cracked NH3) is acknowledged to function as a powerful nitriding medium to realize formation of metal nitride MNx with considerably high N/M ratio x that cannot be achieved through reaction of M with N2 gas. For example, mono-nitride d-MoN of Mo and e-FeNx phase of Fe with x = 0.33 ˜ 0.50 (i. e. hypo-stoichiometric sub-nitride e-Fe2N) were reported to be difficult to prepare in N2 gas environment even at elevated pressure but might be synthesized in flowing NH3 gas at normal pressure when reaction temperature and NH3 gas flow rate were set adequately. In the present work, nitriding experiments for Mo and Fe were carried out in flowing NH3 gas under irradiation with concentrated solar beam. The acquired experimental evidences demonstrated that temperature range for formation of d-MoN was somewhat extended in flowing NH3 gas under heating with concentrated solar beam compared with that under heating in conventional laboratory or industrial electric furnace. On the other hand, no such merit of extending temperature range for formation of e-Fe2N in flowing NH3 gas was detected in the present work under heating with concentrated solar beam.